PENGARUH KINERJA KEUANGAN, UKUR Pengaruh Kinerja Keuangan, Ukuran Perusahaan Dengan Corporate Social Responsibility Sebagai Variabel Moderating Terhadap Nilai Perusahaan - Ni Putu Eka Widiastuti; Rahmasari Fahria; Burhanudin Yusuf Ramadhan (Jurnal Syntax Transformation, 2020)
This study aims to determine the effect of financial performance, firm size with variable moderating corporate social responsibility on firm value. In this research Firm Value measured by Tobin’s Q. The sampel of 10 manufacturing companies listed on the Indonesia Listed Exchange in the 2014-2018 period. The analysis technicque us regression analysis with significance level of 5%. The result of the tests indicated that (1) financial performance has no significant effect on firm value. (2) firm size has no significant effect on firm value. (3) corporate social responsibility has no significant effect on firm value. (4) Corporate Social Responsibility (CSR) as a moderating variable not able to moderate the effect of financial performance and firm value. (5) Corporate Social Responsibility (CSR) as a moderating variable not able to moderate the effect of firm size on firm value.